Synthesis of Mn2O3 Nanoparticles and Determination of Its Inhibition Effect On Sera of Iraqi Patients with Diabetes Mellitus Type-2 and Diabetes Nephropathy - Tawfeeq Ali, Layth; H. Hussein, Hanaa; Abdul Rudha Abbas, Salma (Al-Nahrain Journal of Science, 2024)
Manganese is essential for the synthesis of antioxidant enzymes and metabolic issues in Diabetes type 2 (DMT2), which is a worldwide disease, Chronic metabolic disorders cause insulin resistance, hyperglycemia, and complications like diabetic nephropathy. Arginase converts arginine to ornithine and urea. Increased arginase activity in DMT2 and diabetes nephropathy (DN) which has been linked to kidney damage, and arginase inhibitors can increase NO which is essential to vascular function. However, the molecular mechanisms of arginase disregulation are in DMT2 and DN are still unclear. This study examined the effect of manganese oxide nanoparticles (Mn2O3 NPs) on arginase activity inhibition in serum samples from DMT2 and DN patients. We hypothesized that Mn2O3 NPs alter cell redox status and signaling pathways, affecting DMT2 and DN arginase activity. We used a colorimetric assay to measure arginase activity in 80 serum samples from DMT2 and DN patients treated with different MnO2 NP concentrations to test our hypothesis. The current study characterized nanoparticles using various techniques such as IR, SEM, AFM, XRD, and EDX, which found it within nanoscale nature. Our findings are that Mn2O3 NPs modulate arginase activity specificity in DM2 samples. Suggestions Mn2O3 NPs could be used to develop new treatments for these conditions.